Effect of Neurofeedback on Perceptual Organization, Visual and Auditory Memory in Children with Attention Deficit/Hyperactivity Disorder. - NESAYAN, Abbas; ASADI GANDOMANI, Roghayeh; MOIN, Narges (Iranian Journal of Child Neurology)
Objectives Neurofeedback is a noninvasive treatment that changes brain activity in children with attention-deficit/hyperactivity disorder and thereby improves performance in these children. We examined the effect of neurofeedback on perceptual organization, visual and auditory memory in children with attention-deficit/hyperactivity disorder. Materials & Methods This study was quasi-experimental with pre-test, post-test design, and control group. The sample included 20 children with attention-deficit/ hyperactivity disorder were selected through convenience sampling in Khorramabad, central Iran in 2017. The sample was divided into control and experimental groups. Pre-test included Rey-Osterrieth complex figure and Wechsler digit span. Rey-Osterrieth complex figure test was used to measure perceptual organization and visual memory. Wechsler digit span was used to measure auditory memory. After conducting pre-test, the experimental group participated in neurofeedback training sessions. Theta/Beta protocol was applied for all participants. The control group did not receive any intervention. Then post-test was conducted on two groups. Results Neurofeedback training significantly improved visual memory (P<0.001) but neurofeedback training had no significant effect on the perceptual organization (P>0.05). Moreover, neurofeedback training enhanced auditory short-term memory and auditory working memory (P<0.05). Conclusion Neurofeedback improved neurocognitive abilities in children with attention-deficit/hyperactivity disorder.